Histopathology of Fusarium wilt of staghorn sumac (Rhus typhina) caused by Fusarium oxysporum f. sp. callistephi race 3. II. Characteristics of opaque matter associated with extensive host cell and cell wall alterations - Ouellette, Guillemond; Rioux, Danny; Simard, Marie (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2005)
AbstractLight and transmission electron microscopy observations of staghorn sumac plants inoculated or naturally infected with Fusarium oxysporum f. sp. callistephi are reported. One aspect of infection was the presence of large intercellular masses of opaque matter (OM) in middle lamellae between ray cells and/or fibres, often bypassing several intercellular areas; similar OM confluent with the intercellular OM also occurred in secondary walls and in the periphery of numerous cells. A gradual increase in the abundance of the OM in host tissues vertically from the inoculation point and then radially was noted over infection time and was related to host wall and cell alterations. In the region of recently deposited tissue, the OM was associated with pronounced cell hyperplasia and hypertrophy. The OM was delimited by thin, compact bands, and when it was less compact, displayed opaque particles and other fine structures. No indications were obtained that it contained or had contained intact or altered organelles. The DNA probe bound to OM in middle lamellae and in cell periplasmic areas, and to material of a similar texture lining vessel walls. Samples from Fusarium-infected plants, incubated on an agar medium before fixing to determine from which elements the pathogens could develop, displayed bodies as the sole elements present in mature xylem cells and in intercellular areas. These bodies were delimited by membranous structures and profiles of a wall layer and contained opaque particles and areas of fine structures. Certain inter- or intracellular fungal cells in the same tissue frequently had similar content. In the light of these observations it is proposed that the OM is primarily of a pathogen rather than of a host origin.